The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3346/jkms.2017.32.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Cardiovascular Characteristics of Adult Patients with Chronic Kidney Disease from the KoreaN Cohort Study for Outcomes in Patients With Chronic Kidney Disease (KNOW-CKD)

Abstract: Cardiovascular disease (CVD) is the most common cause of death in patients with chronic kidney disease (CKD). We report the baseline cardiovascular characteristics of 2,238 participants by using the data of the KoreaN Cohort Study for Outcomes in Patients With Chronic Kidney Disease (KNOW-CKD) study. The cohort comprises 5 subcohorts according to the cause of CKD: glomerulonephritis (GN), diabetic nephropathy (DN), hypertensive nephropathy (HTN), polycystic kidney disease (PKD), and unclassified. The average e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The KNOW-CKD is a nationwide, multicenter, prospective, observational cohort study from nine tertiary hospitals in Korea. The rationale, design, methods, and protocol summary of the study (15) and baseline characteristics of the participants (16)(17)(18)(19)(20) are described elsewhere. Briefly, patients with CKD stages 1-5 (nondialysis) ages 20-75 years old were enrolled between 2011 and 2015.…”
Section: Study Participantsmentioning
confidence: 99%
“…The KNOW-CKD is a nationwide, multicenter, prospective, observational cohort study from nine tertiary hospitals in Korea. The rationale, design, methods, and protocol summary of the study (15) and baseline characteristics of the participants (16)(17)(18)(19)(20) are described elsewhere. Briefly, patients with CKD stages 1-5 (nondialysis) ages 20-75 years old were enrolled between 2011 and 2015.…”
Section: Study Participantsmentioning
confidence: 99%
“…It is also associated with increased risk for cardiovascular disease and all-cause mortality in patients with diabetes (2). Therefore, preventing the development and progression of DKD is important when treating diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline characteristics were compared with similar studies representing various geographical locations across the world (Table 3). [9][10][11][12][13][14] The Darling Downs and its surrounding areas, where most patients came from, represents part of regional, rural and remote Queensland and consists of stable farming and mining community in contrast to the study population reported in MINTS-PAH cohort, which was predominantly urban. 14 DDH CKD population is older and predominantly Caucasian with 9.8% being Aboriginal.…”
Section: Discussionmentioning
confidence: 91%
“…Our report is the first comprehensive individual site data on a pre‐dialysis cohort recruited into the CKD.QLD Registry. The baseline characteristics were compared with similar studies representing various geographical locations across the world (Table ) …”
Section: Discussionmentioning
confidence: 99%